72 Ectopic Beats – Frequent, Troublesome and not to be Dismissed. (6th June 2015) - Morritt, Jennifer; Howlett, Philippa; Greswell, Laura; Leatham, Edward
Abstract : Purpose: Palpitations are among the most common reasons for referral to a cardiology clinic. Premature ectopic beats have previously been shown to be the most frequent finding in this population and serious arrhythmias are less commonly encountered. Despite a lack of clinical prognostic significance associated with the majority of ectopic beats, they can cause considerable distress and anxiety for the patient and therapeutic management can be challenging. The impact on quality of life and psychological well-being of those affected is under-recognised. We aim to determine whether the symptom burden of individuals with ectopics differs significantly from those with sustained arrhythmias. Methods: 94 patients with palpitations (mean age = 65 years; 68% female) were referred to a community arrhythmia screening clinic. They were contacted by an experienced cardiac nurse and a brief medical history was taken to include: symptom frequency, severity and character as well as any significant past medical history. Patients rated how troublesome their symptoms were on a scale between 0 and 3 in line with the AF (atrial fibrillation) clinical evaluation scale (European Heart Rhythm Association). Patients were monitored with both an automated cardiac event recorder for 1-week (R. Test Evolution 4, Novacor. They also used a handheld ECG monitor (OMRON Portable ECG Monitor HCG-810) for a 3-month period, recording their heart rhythm for 30-seconds twice a day and when they experienced symptoms. Recordings were analysed and a final diagnosis was ascribed by a cardiologist Results: The most common confirmed diagnosis was ectopic beats, seen in 45 patients (48%). Specifically 17 (18%) were documented to have atrial ectopics, 10 (11%) ventricular ectopics and 18 (19%) both atrial and ventricular ectopics. Additionally 22 patients (23%) were diagnosed with sustained arrhythmias (17% AF, 5% atrial flutter, 1% atrioventricular nodal reentrant tachycardia) and 27 (29%) patients were shown to be in sinus rhythm. Patients found to have ectopic beats had an equivalent symptom severity score when compared to those with sustained arrhythmias (1.3 ± 0.6 vs. 1.53 ± 0.59; p = 0.10). Conclusion: A pronounced symptomatic burden was found in those with seemingly benign ectopic beats. Patient symptom severity, as well as prognosis, is an important factor to consider when addressing long-term management.